(untitled) (Hekima Review, 2016)
Recognizing the prominence of education, the Catholic Church, particularly in the post Tridentine era, has taught that the primary end of marriage inter alia is education of children. She argues that parents are the primary educators of their children and, therefore, they should be the ones to expose their children to education including Sexuality Education. As a matter of fact, this is the ideal, which should be attained by the parents, since they have authority over their children. In Kenya, the parents in most cases have not been able to attain this epitome due to multifaceted and complex factors. As a result, Sexuality Education has technically been neglected. Evidently, the debate on Sexuality Education seems to be recurring persistently, begging for due attention. is paper intendsto examine the Church’s position contrasting it with lived reality. Recognizing the gap due to neglect by parents, the paper proposes school teachers as supplement to parents in teaching Sexuality Education.